A Convenient One-Pot Synthesis of 1-Aryl-Substituted 4-Iodopyrazol-3-Ols via Aromatisation and Oxidative Iodination Reactions. (January 2018) - Liu, Jingjing; Yang, Shanguang; Dong, Ruimei; Jin, Zhudan; Wang, Mingliang
A convenient and economical one-pot synthesis of a series of new 1-aryl-substituted 4-iodopyrazole-3-ols from easily available pyrazolidin-3-ones in the presence of sodium iodide, 30% solution of hydrogen peroxide and a catalytic amount of sulfuric acid in dichloromethane via aromatisation and oxidative iodination reactions are described. This protocol has the advantages of high atom economy, cost-effectiveness, short reaction time and environmental friendliness.